La identidad ecuatoriana por oposición y ofensa. El olvido del mestizo (Artículos de Investigación) - Padilla Sigcha, Kevin Alexander K. (2019)
The present job focuses on analyzing the construction of Ecuadorian national identity, which reference has been made to the “mestizo” concept. The result of an external stimulus as the Venezuelan migration that allows to significantly track the representations of identity around implication of a nation project. From the xenophobic problem generated in social networks through the internet, these manage to revive ethnic complexes that bare and make explicit the mestizo being.